2002
DOI: 10.1117/12.460420
|View full text |Cite
|
Sign up to set email alerts
|

Eyeglass: a very large aperture diffractive space telescope

Abstract: This is a preprint of a paper intended for publication in a journal or proceedings. Since changes may be made before publication, this preprint is made available with the understanding that it will not be cited or reproduced without the permission of the author.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 0 publications
0
26
0
1
Order By: Relevance
“…A 25-100 m aperture diffractive lens is to be deployed on orbit. 5,6 Two proposed missions that intend to generate large kilometer size baselines are the NASA Goddard Stellar Imager 7 and the NASA JPL study on the proposed Terrestrial Planet Finder (TPF). 8 Both of these concepts utilize a formation of free-flying spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…A 25-100 m aperture diffractive lens is to be deployed on orbit. 5,6 Two proposed missions that intend to generate large kilometer size baselines are the NASA Goddard Stellar Imager 7 and the NASA JPL study on the proposed Terrestrial Planet Finder (TPF). 8 Both of these concepts utilize a formation of free-flying spacecraft.…”
Section: Introductionmentioning
confidence: 99%
“…At the Lawrence Livermore National Laboratory(LLNL),they are working to develop a new type of space telescope ,based upon the use of diffractive optics [1][2][3][4] Obervation screen However, the foremost task for developing large aperture diffractive telescope is to choose a reasonable stitching pattern on the diffractive lens, because it not only affects stitching difficulty and image quality, but also affects the alignment, testing, as well as manufacturing process. Due to this reason, in this paper a study is made on the technology of stitching for large diffractive telescope.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, DOE-based primary lenses show loose surface shape tolerance and are lightweight. In 1999, Hyde first proposed the Eyeglass telescope system, which uses a large-diameter diffractive lens as the primary lens and a separate telescope as the mobile eyepiece [7]. Based on this sketch, Serre et al designed a ground-based prototype and tested the telescope system.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, Hyde proposed the MOIRE system, which shares the same structure as the Eyeglass. From his studies, he demonstrated that it is very difficult to fabricate large-diameter DOEs directly, and the best way to fabricate them is to process small diffractive element sections and then properly stitch them together [9].…”
Section: Introductionmentioning
confidence: 99%